Structural changes at microtubule ends accompanying GTP hydrolysis: Information from a slowly hydrolyzable analogue of GTP, guanylyl (α,β)methylenediphosphonate - Müller-Reichert, Thomas (The National Academy of Sciences, 1998)
Microtubules are dynamic polymers that interconvert between periods of slow growth and fast shrinkage. The energy driving this nonequilibrium behavior comes from the hydrolysis of GTP, which is required to destabilize the microtubule lattice. To understand the mechanism of this destabilization, cryo-electron microscopy was used to compare the structure of the ends of shrinking microtubules assembled in the presence of either GTP or the slowly hydrolyzable analogue guanylyl (α,β)methylenediphosphonate (GMPCPP). Depolymerization was induced by cold or addition of calcium. With either nucleotide, we have observed curled oligomers at the ends of shrinking microtubules. However, GDP oligomers were consistently more curved than GMPCPP oligomers. This difference in curvature between depolymerizing GDP and GMPCPP protofilaments suggests that GTP hydrolysis is accompanied by an increase in curvature of the protofilaments, thereby destabilizing the lateral interactions between tubulin subunits in the microtubule lattice.